Conceptual Analysis of the Time Token and Talking Stick Learning Models in Increasing Student Learning Activity in Islamic Religious Education Learning - Muhammad Rifkhi Maulana; Elly Kurniawati; Imam Syafe’i; Eti Hadiati; Ratu Vina Rohmatika (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study is motivated by the low level of student learning activeness in Islamic Religious Education (PAI), which is still dominated by teacher-centered learning approaches. The purpose of this study is to conceptually analyze the effectiveness of the Time Token and Talking Stick learning models in improving student learning activeness. This study employs a qualitative approach using a library research method by reviewing relevant scientific literature from the last five years. Data analysis techniques include data reduction, data display, and conclusion drawing. The findings reveal that the Time Token model effectively enhances learning activeness through equitable participation in classroom discussions. Meanwhile, the Talking Stick model improves students’ cognitive readiness, confidence, and spontaneous participation. Comparatively, both models have distinct yet complementary characteristics: Time Token emphasizes equitable participation, while Talking Stick focuses on cognitive readiness. The integration of these models contributes to creating active, dialogic, and meaningful PAI learning.